Postgraduate research collaboration UiTM – UNHAS - Mohd Nasir, Ahmad Merza; Mohd Rasul, Ruhisy Syakirah; Ibrahim, Norkasihan (Faculty of Pharmacy, 2026)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam Campus recently welcomed a delegation of postgraduate students and academic staff from Universitas Hasanuddin (UNHAS), Indonesia, as part of a three- day academic mobility programme held from the 26 to the 28 of January2026. The delegate was led by Professor Yulia Yusrini Djabir. Organised by the Postgraduate Skill Development and Recruitment Committee (PG-RAISE) and the Postgraduate Student Committee, the visit marked an important milestone in strengthening regional postgraduate research collaboration and academic networking.